Analisis Zerumbone Dalam Zingiber zerumbet Dan Aktivitas Penghambatannya Terhadap Bakteri Mycobacterium tuberculosis: Analysis of zerumbone in Zingiber zerumbet and inhibitory activity against Mycobacterium tuberculosis - Lallo, Subehan; Kasim, Syaharuddin; Tayeb, Rosany; Hasan, Asril Damiyanto; Sere, Hartina; Ismail, Ismail; Arifin, Tamsil (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2018)
Zerumbone has been reported for their several biological activities. In our interest to this compound, we have identified and analyzed its content in Zingiber zerumbet, a medicinal plant from Indonesian traditional medicine and investigated its inhibitory activity against Mycobacterium tuberculosis, a known infection bacteria of tuberculosis. Analysis of zerumbone was performed with densitometry to leave, rhizome, flower, and stem of Z. zerumbet which was extracted with various solvent system and extraction methods to determine the best method to isolate zerumbone from Z. zerumbet. Result showed that the highest zerumbone was in rhizome while was not observed in other part. Analysis with various solvent and extraction methods showed the highest yield of zerumbone can be extracted by n-hexane (maceration) and reflux extraction method (methanol). Furthermore, inhibitory activity of zerumbone against M. tuberculosis was tested using Lowenstein Jensen medium by counting the number of M. tuberculosis colony growth in medium. Resulted inhibitory activity of zerumbone at all test concentration (0.5, 0.1, 0.05, 0.01, 0.005%) with the growth of 10, 12, 14, 15, and 50 colonies of M. tuberculosis was observed, respectively. This is indicate that zerumbone can be used as an alternative choice for treatment tuberculosis in the future.